Strategies for Implementing The Project-Based Learning Model in Improving Creative Writing Skills in Indonesian Language Learning - Nurasman, Muhammad Syaiful; Alfalah, Adib (Raja Zulkarnain Education Foundation, 2025)
Creative writing is an essential skill in Indonesian language learning that supports the development of imagination, expression of ideas, and critical thinking. However, this skill is still a challenge for many learners due to the low relevance of the material to real life and the lack of contextualized learning approaches. This article aims to examine the implementation strategy of the Project-Based Learning (PjBL) model in improving creative writing skills through a systematic literature review approach of ten scientific articles published in 2019-2024. The results show that PjBL is effective in creating an active, collaborative, and reflective learning environment by engaging learners in writing projects based on hands-on experiences. The article formulates four main principles of PjBL implementation strategies, namely contextual exploration, collaboration, production-revision of work, and publication and reflection. Despite its great potential, the implementation of PjBL also faces challenges such as time constraints, teacher competence, and the adequacy of supporting facilities. Therefore, the success of this strategy is determined by adaptive learning design and adequate institutional support. The findings are expected to be a theoretical and practical contribution in the development of creative writing literacy relevant to 21st century learning needs.